Impact and interpretation of different measures of genetic diversity in inbred lines applied to crop breeding - Cendoya, Maria Gabriela; Grondona, Martín; Zambelli, Andrés (Brazilian Journal of Biometrics, 2025)
The application of molecular genetics in crop breeding has grown significantly, largely due to the success of molecular breeding, which utilizes genotype-based approaches to achieve substantial genetic improvements with favorable cost-effectiveness. A successful molecular breeding strategy involves thorough genotyping, enabling detailed genetic characterization of target germplasm, including genetic diversity analysis, relationships, and population structure. Genotype-based methods, favored for their stability and independence from environmental factors, are preferred over phenotype-based approaches. Genetic diversity is assessed by comparing individual genotypes within and across populations, using statistical methods to calculate genetic distances or similarities. This study focuses on establishing a unified framework to compare and evaluate common similarity measures and their relation to distance metrics, specifically in diploid inbred lines genotyped with biallelic SNPs, for use in genetic improvement efforts.